Total Arthroscopic Resection of the Talocalcaneal Coalition in Adults: Key Points of Surgical Technique - Yiyuan Sun; Wufeng Cai; Xihao Huang; Jian Li; Qi Li (Orthopaedic Surgery)
Objective Potential disadvantages of open technique for talocalcaneal coalition (TCC) include a risk of wound infection, opioid drug dependence, and prolonged hospitalization. The purpose of this study was to retrospectively evaluate the effectiveness and safety of endoscopic resection of the TCC. Methods A retrospective study from June 2019 to February 2023was conducted on 16 consecutively admitted patients who were diagnosed by imaging to have TCC for whom conservative treatment had failed and who undergone arthroscopic resection. The mean age of this cohort was 31.56 ± 10.39 years (range, 16–57 years). The mean follow‐up period was 38.93 ± 15.69 months (range, 11–59 months). The site of the coalition, comorbidities, satisfaction with treatment, visual analog scale (VAS), and American Orthopedic Foot and Ankle Society (AOFAS) Ankle–Hindfoot scale scores were evaluated pre‐ and postoperatively. Preoperative magnetic resonance imaging (MRI) scans were used to categorize the coalition according to the Lim classification. Postoperative computed tomography (CT) scans were used to assess recurrence. The distribution of TCC cases according to the Lim classification was type I in one case, type II in four cases, and type III in 11 cases. Results The site of coalition involved the middle facets in seven patients, the posterior facets in three patients, and both the above sites in six patients. All patients underwent total arthroscopic resection of TCC. An auxiliary mini‐incision was made for three patients due to serious tibial nerve compression. Radiographics showed that the coalition disappeared and pain was relieved postoperatively. The mean VAS score decreased from 4.31 ± 1.54 to 1.81 ± 0.98 points (p < 0.001). The mean AOFAS ankle‐hindfoot score improved from 65.56 ± 5.82 to 87.31 ± 6.30 points (p < 0.001). Fifteen patients were satisfied with the procedure, and one patient experienced numbness after surgery. No recurrence was reported based on CT scan and clinical results up to the end of the study. Conclusion Surgical reconstruction employing total arthroscopic resection of TCC can achieve significant functional and radiographic improvements and symptom relief in selected patients with TCC. Auxiliary mini‐incisions were necessitated in complex situations.